TANTANGAN PENGELOLAAN SUMBER DAYA MANUSIA DALAM PROGRAM INKUBATOR BISNIS; STUDI KASUS DI POLITEKNIK NEGERI MANADO - Rondonuwu, Bervie Fransel; Maramis, Diana Roweina Suzana; Langi, Cysca J.; Wollah, Meidy; Pessak, Romana Octavia Debora (Jurusan Administrasi Bisnis Politeknik Negeri Manado, 2026)
This study aims to explore and analyze the challenges of human resource (HR) management in the business incubator program at Politeknik Negeri Manado, a vocational higher education institution in North Sulawesi, Indonesia. Using a qualitative case study design based on Robert K. Yin's (2018) framework, data were collected through semi-structured in-depth interviews with seven key informants comprising the incubator coordinator, faculty mentors, the department head, and the vice-director for student affairs. Document analysis served as a supplementary data source. Thematic analysis following Braun and Clarke's (2006) six-phase procedure was applied to the data. Findings reveal four major HR challenges: (1) role conflict experienced by lecturers serving simultaneously as incubator managers; (2) insufficient managerial and entrepreneurial competence among incubator staff (3) the absence of a formal recruitment and assignment system for incubator managers; and (4) limited access to capacity-building training. These findings contribute to the underexplored literature on HR management in vocational college incubators in Eastern Indonesia and provide actionable recommendations for institutional policymakers to strengthen the sustainability of business incubator programs.